Revision of the types of male Sciaridae (Diptera) described from Australia by F.A.A. Skuse - Broadley, Adam; Kauschke, Ellen; Mohrig, Werner (Zootaxa, 2016)
A total of 27 male sciarid types described by Skuse (1888 and 1890), held in the Australian National Insect Collection, Canberra, and the Australian Museum, Sydney, were remounted and examined microscopically. Of these, 25 species were described as Sciara Meigen, one as Zygoneura Meigen and one as Trichosia Winnertz. Revision of these species revealed the following: 13 species belong to the genus Bradysia Winnertz (B. amabilis, B. conjuncta, B. crassicornis, B. exsequialis, B. frequens, B. froggatti, B. luctifica, B. maesta, B. mastersi, B. ornatula, B. pernitida, B. pictipes, B. unica), 1 species to the genus Corynoptera Winnertz (C. minutela), 4 species to the genus Austrosciara Schmitz & Mjöberg (Aus. infrequens, Aus. montivaga, Aus. spectabilis, Aus. winnertzi), 2 species to the genus Pseudolycoriella Menzel & Mohrig (Psl. cavatica, Psl. ignobilis), 1 species to the genus Pseudozygomma Mohrig (Pseudoz. maculipennis), 1 species to the genus Sciara Meigen (Sc. tryoni), and 1 species to the genus Scythropochroa Enderlein (Scyth. macleayi). In total 26 species were new combinations. Eight species names were declared as new synonyms: Bradysia pictipes (Skuse, 1888) = Sciara notata Skuse, 1888 syn. n. and = Bradysia seticornis Vilkamaa, Hippa & Mohrig, 2012 (from New Caledonia) syn. n.; Bradysia conjuncta (Skuse, 1890) = Sciara serenipennis Skuse, 1890 syn. n.; Pseudolycoriella cavatica (Skuse, 1888) = Sciara familiaris Skuse, 1888 syn. n. and = Sciara festiva Skuse, 1888 syn. n.; Bradysia luctifica (Skuse, 1888) = Bradysia planistylata Vilkamaa, Hippa & Mohrig, 2012 syn. n.; Sciara tryoni Skuse, 1890 = Sciara insulana Vilkamaa, Hippa & Mohrig, 2015 syn. n. (both species are from New Caledonia); Austrosciara winnertzi (Skuse, 1888) = Sciara rufulenta Edwards, 1927 syn. n. (from New Zealand). Lectotype specimens were designated for 17 species in order to fix the names.